The effect of the Bologna Process on the duration of studies - Katharina Lerche (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
This paper evaluates the effect of replacing traditional German five-year degrees with three-year bachelor programs on the duration until graduation and dropping out of university. Using an extensive dataset containing detailed administrative data on more than 9000 students, competing risks models are estimated. The results reveal that the Bologna process reduced the duration until graduation in absolute and relative terms, indicating that one of the reforms main objectives was achieved. In addition, there is a favorable impact of being enrolled in a bachelor program on the probability of dropping out of university for students enrolled at the faculty of humanities. However, the results concerning university drop out are less conclusive for the other faculties.
Keywords: I21; I28; H75; J24; 330; tertiary education; Bologna process; bachelor; survival analysis; competing risks